1989
DOI: 10.1093/mutage/4.4.265
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of dose-response parameters for radiation-induced acentric fragments and micronuclei observed in cytokinesis-arrested lymphocytes

Abstract: We employed cytochalasin B to block cytokinesis in human lymphocytes exposed to 220 kV X-radiation. When 3 micrograms/ml of cytochalasin B was used, most cells escaped the block whereas at 6 micrograms/ml greater than 90% of the mitogen-responsive cells became binucleate. Using the higher concentration of cytochalasin B, we observed a linear-quadratic (i.e. Y = gamma + alpha D + beta D2) dose dependency for X-ray-induced micronuclei (MN) in preparations from three donors. When dose-response parameters were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
2
6

Year Published

1992
1992
2001
2001

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(52 citation statements)
references
References 0 publications
6
36
2
6
Order By: Relevance
“…Moreover, radiosensitivity has frequently been asssessed by measuring DNA double-strand breaks using electrophoretic (Foray et al, 1997), cytogenetic (Little®eld et al, 1989) techniques, or cytokinesis-block micronucleus assay (Fenech, 1997). Therefore, it is essential to develop molecular multiparametric approaches in order to improve knowledge of cellular pathways involved in response to radiation, since such biomarkers could be critical for the follow-up of cancer patients treated by radiotherapy, or of healthy people accidentally exposed to radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, radiosensitivity has frequently been asssessed by measuring DNA double-strand breaks using electrophoretic (Foray et al, 1997), cytogenetic (Little®eld et al, 1989) techniques, or cytokinesis-block micronucleus assay (Fenech, 1997). Therefore, it is essential to develop molecular multiparametric approaches in order to improve knowledge of cellular pathways involved in response to radiation, since such biomarkers could be critical for the follow-up of cancer patients treated by radiotherapy, or of healthy people accidentally exposed to radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Many fewer kinetochore-containing MN were identified after X-irradiation of human melanoma cells (Weissenborn and Streffer, 1991) or γ-irradiation of human lymphocytes (Littlefield et al, 1989) or fibroblasts (Cornforth and Goodwin, 1991). However, the rate of exposure was associated with the probability of acentric fragments being included in the MN.…”
Section: Discussionmentioning
confidence: 99%
“…However, the rate of exposure was associated with the probability of acentric fragments being included in the MN. With acute high doses of radiation exposure, acentric fragments would be less likely to be incorporated into single MN separately and there would be a tendency to form MN with multiple acentric fragments (Littlefield et al, 1989). If this could be applied to low dose rate exposure of the subjects in this study, acentric fragments could be fully expressed as independent MN.…”
Section: Discussionmentioning
confidence: 99%
“…However, at doses above 0.1 Gy there was no significant further increase of the mean DNA content (data not shown). Littlefield et al (12) observed a dose-dependent increase of the proportion of large micronuclei in human lymphocytes irradiated in vitro with X-rays. They took this observation as an indication that at higher doses multiple acentric chromosome fragments are enclosed in a single micronuclear membrane.…”
Section: Discussionmentioning
confidence: 99%